The Relationship of Fear of Death Between Neuroticism and Anxiety During the Covid-19 Pandemic - Pérez-Mengual, Núria; Aragonés-Barbera, Inmaculada; Moret-Tatay, Carmen; Moliner-Albero, Adoración Reyes (Frontiers in Psychiatry, 2021)
After a lockdown, particularly one where human life is at risk, there are expected to be psychological consequences. The examination of personality traits, where different adaptative and non-adaptative behaviors in the face of adversity are expected, is our interest. The aim of this research was to analyze the role fear of personal death played during the Covid-19 outbreak in relation to personality and anxiety. The main results can be described as follows: women displayed higher scores on anxiety and fear of personal death; gender, fear of personal death, neuroticism, and extraversion predicted anxiety; in men, the fear of personal death mediated the relationship between neuroticism and anxiety.